2013
DOI: 10.5430/jnep.v3n12p187
|View full text |Cite
|
Sign up to set email alerts
|

Self-centeredness or patient-centeredness–final year nursing students’ experiences of learning at a clinical education ward

Abstract: Background: Different types of clinical education wards with the aim of facilitating transition from student to professional have been established giving students more autonomy and responsibility. Studies report positive effects but deeper understanding concerning how clinical education wards can contribute to learning for students nearing graduation is needed. Aim:To explore final year nursing students' experiences of learning when they are supported to take care of patients independently. Methods:The context… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 43 publications
(58 reference statements)
0
12
0
Order By: Relevance
“…Supervisors’ role as facilitators has been emphasized as important by Brammer [ 11 ]. Having a team of supervisors is appreciated by the students as it enhances the students’ thinking and reflecting on patient care and on their own learning, as well as further developing their existing knowledge and skills [ 8 , 9 , 28 ]. However, it has also been shown by Manninen et al [ 9 ] that students have concerns about the team of supervisors and that they experience feelings of ambivalence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Supervisors’ role as facilitators has been emphasized as important by Brammer [ 11 ]. Having a team of supervisors is appreciated by the students as it enhances the students’ thinking and reflecting on patient care and on their own learning, as well as further developing their existing knowledge and skills [ 8 , 9 , 28 ]. However, it has also been shown by Manninen et al [ 9 ] that students have concerns about the team of supervisors and that they experience feelings of ambivalence.…”
Section: Discussionmentioning
confidence: 99%
“…They are units with a pedagogical framework focusing on training students in real clinical settings with the support from supervisors [ 4 , 5 ]. While previous research [ 6 9 ] has focused on students’ perspectives on learning at clinical education wards, the present study investigates the supervisors’ perspective.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Students' understanding of patient‐centred care and the role of nursing education programmes are important in the teaching–learning process. Manninen, Scheja, Welin Henriksson, and Silén () in regard to the students' self‐centred and patient‐centred experiences stated that self‐centred care for students is considered to be a tool for learning and a routine nursing practice. Therefore, it is vitally important to consider the concept of patient‐centred care in nursing education programmes (Manninen et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Students in our study demonstrated a variety of reflections in their use of mimicry drawn from the video cases, centred on their ability of how to handle the situation. Correspondingly, mimicry in students has previously been identified as a method to cope with stressful transitions (62)(63)(64)(65).…”
Section: Passive Roles Influencing a Self-centred Reflectionsmentioning
confidence: 99%